COMPARISON OF RAYLEIGH WAVE CHARACTERISTICS ON SUPERCONDUCTING GRAVIMETER AND SESIMOMETER LHZ RECORDINGS - MARISKA NATALIA RANDE; Mahmud Yusuf; Alexander F. T Parera (Pusbindiklat - LIPI, 2019)
The vibrations of an earthquake can be properly recorded by the gravimeter. As a Gravimeter, Superconducting Gravimeter (SG) has a very high accuracy; slightly different with general gravimeter. Rayleigh wave is the wave with the largest amplitude in earthquake, so it will be clear on SG tape. In this research, we use certain superconducting gravimeter (SG) and Seismometer LHZ, spread over several locations around the world; just to know more about Mw > 6 earthquake. Tidal value reduction were applied on SG’s recording in order to get true gravity value. Then we did time-integral to get velocity and displacement. By using spectrogram function, we can display frequency of SG and LHZ. The amplitude of the Rayleigh wave recorded on the SG is smaller than that recorded on the LHZ and has signal correlation > 7.0. In any case of Rayleigh Global waves, SG is able to record clearly the phase of Rayleigh wave to R7 phase. While LHZ only records up to the R5 phase. The spectrograph analysis reinforces the differences in the viewing screens of SG and LHZ Rayleigh Global waves in the frequency domain, R7 recorded on SG has a frequency range of 0.002 Hz to 0.006 Hz. Based on the results of Rayleigh wave analysis on the SG record and its comparison with the LHZ record it can be concluded that SG has a high level of sensitivity and stable when recording Rayleigh waves.